Evolution of the Global Temperature Structure of the Solar Corona During the Minimum between Solar Cycles 23 and 24 - Nuevo, Federico Alberto (2013)
The combination of Differential Emission Measure Tomography (DEMT) with extrapolation of the photospheric magnetic field allows determinatio/n of the electron density and electron temperature along individual magnetic field lines. This is especially useful in quiet Sun (QS) plasmas where individual loops cannot otherwise be identified. In Paper I (Huang et al. 2012), this approach was applied to study QS plasmas during Carrington rotation (CR) 2077, at the minimum between solar cycles (SC)-23 and 24. In that work, two types of quiet QS coronal loops were identified: ``up" loops in which the temperature increases with height, and ``down" loops in which the temperature decreases with height. While the first ones were expected, the latter ones were a surprise and, furthermore, were found to be ubiquitous in the low-latitude corona. In the present work we extend the analysis to 11 CRs around the last solar minimum. We find that the ``down´´ population, always located at low-latitudes, was maximum at the time when the sunspot number was minimum, and the number of down loops systematically increased during the declining phase of SC-23 and diminished during the rising phase of SC-24. ``Down´´ loops are found to have systematically larger values of $eta$ than do ``up´´ loops. These discoveries are interpreted in terms of excitation of Alfv´en waves in the photosphere, and mode conversion and damping in the low corona.